Transnational Litigation - Mohan, Mahdev (Institutional Knowledge at Singapore Management University, 2014)
In 2013, the United States Supreme Court held that it had no jurisdiction to hear a case relating to conduct which occurred outside U.S. territory, and that concerned a suit brought against a company based outside the U.S. Today referred to as the ‘Kiobel decision’, it represents a significant shift of the aperture of transnational corporate accountability away from the U.S. – which generally has been the default venue – and towards regional and foreign jurisdictions where violations occur, or where responsible beneficiaries of the wrongdoings reside or conduct their businesses. Mahdev Mohan, an Assistant Professor of Law at the SMU School of Law, has been involved in award-winning research and writing in the fields of international law and conflict resolution. His international litigation before the UN-backed Khmer Rouge Tribunal has also earned him Singapore's Outstanding Young Person Award for his contributions to the promotion of human rights. In his recent scholarly article entitled ‘The Road to Song Mao: Transnational Litigation from Southeast Asia to the United Kingdom’, published in a special issue of the American Journal of International Law, Assistant Professor Mohan wrote that anxieties caused by the U.S. Supreme Court’s decision should not eclipse the fact that redress can, and at times should, be secured in the UK and elsewhere. In this podcast, he shares his insights on transnational litigation and examines the learning points that businesses, policy makers and courts can draw from the Song Mao case.